Evidencing subtle faults in deep seismic reflection profiles: Data pre-conditioning and seismic attribute analysis of the legacy CROP-04 profile - Ercoli, Maurizio; Carboni, Filippo; Akimbekova, Assel; Carbonell, Ramon Bertran; Barchi, Massimiliano Rinaldo (Frontiers in Earth Science, 2023)
Legacy seismic reflection data constitute an infrastructure of tremendous value for basic research. This is especially relevant in seismically hazardous areas as they can significantly contribute to the seismotectonic characterization of the region. The quality of the data and the image can be effectively improved by using modern tools, like pre-conditioning techniques and seismic attributes. The latter are extensively used by the hydrocarbon exploration industry, but are still poorly applied to the study of active faults. Pre-conditioning filters are effective removing random noise which hampers the detection of subtle geologic structures (i.e. normal faults). In this work, a workflow including pre-conditioned seismic attributes is used to improve the quality of the CROP-04 deep seismic reflection profile. CROP-04 was acquired in the 1980s across the Southern Apennines Mountain range, one of the most hazardous seismically active regions in Italy. The results show the capability to extract, from low-resolution legacy data, subtle seismic fabrics that corresponding to a dense network of fault sets. These seismic signatures and the enhanced discontinuities disrupting the reflections, invisible in the original data, well correlate with the main regional normal faults outcropping at the surface. Moreover, the data reveal higher structural complexity, due to many secondary synthetic and antithetic structures, which are useful to model the local and regional distribution of the deformation and to possibly guide future field mapping of active faults. This proposed approach and workflow can be extended to seismotectonic studies of other high-hazard regions worldwide, where seismic reflection data are available.